2008
DOI: 10.1590/s0103-50532008000300020
|View full text |Cite
|
Sign up to set email alerts
|

Non-aromatic hydrocarbons in recent sediments of Sepetiba and Ilha Grande Bays, Brazil

Abstract: Realizou-se uma investigação nas Baías de Ilha Grande e de Sepetiba sobre a natureza dos hidrocarbonetos não-aromáticos (NAH) em seus sedimentos. A mistura complexa não resolvida (UCM) constituiu de 50 a 90% da concentração dos NAH, que variou entre 2,5 µg g -1 e 193,8 µg g -1 . Na maior parte das amostras a distribuição dos n-alcanos foi unimodal com predomínio de compostos de número ímpar de átomos de carbono e máximos em nC 29 e nC 31 . Monolefinas ocorreram em baixas concentrações, enquanto as poliolefinas… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0
7

Year Published

2009
2009
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(11 citation statements)
references
References 26 publications
0
4
0
7
Order By: Relevance
“…This high average could be attributed to the nature of the sampling locations since Imb2 station is located beside the wharf of the port with lower hydrocarbon inputs from higher plants, however, station Ita1, which is located next to the Itajaí-Açu River mouth and thus receives higher hydrocarbon inputs to the sediment from the water column. In general, the concentrations calculated in our study were higher than those observed for sediment samples collected from other marine areas, such as the southern Okinawa Trough (3.0-9.4 μg g −1 of TOC; Jeng 2007), the Yellow River mouth (920-2,740 μg g −1 of TOC; Zhang et al 2008), northeastern Taiwan (96.4-445.0 μg g −1 of TOC; Jeng et al 2003), and the Ilha Grande and Sepetiba Bays (0.07-0.60 μg g −1 of TOC; Figueiredo et al 2008).…”
Section: N-alkanes and Isoprenoid Hydrocarbonsmentioning
confidence: 99%
“…This high average could be attributed to the nature of the sampling locations since Imb2 station is located beside the wharf of the port with lower hydrocarbon inputs from higher plants, however, station Ita1, which is located next to the Itajaí-Açu River mouth and thus receives higher hydrocarbon inputs to the sediment from the water column. In general, the concentrations calculated in our study were higher than those observed for sediment samples collected from other marine areas, such as the southern Okinawa Trough (3.0-9.4 μg g −1 of TOC; Jeng 2007), the Yellow River mouth (920-2,740 μg g −1 of TOC; Zhang et al 2008), northeastern Taiwan (96.4-445.0 μg g −1 of TOC; Jeng et al 2003), and the Ilha Grande and Sepetiba Bays (0.07-0.60 μg g −1 of TOC; Figueiredo et al 2008).…”
Section: N-alkanes and Isoprenoid Hydrocarbonsmentioning
confidence: 99%
“…These values are comparable to unpolluted (< 100 µg g -1 dw) 4 and polluted coastal environments around the world. [30][31][32] Organic carbon normalization revealed that hydrocarbon concentrations in these samples may be underestimated when expressed as dry weight, notably in SM1A (NA concentration of 4.8 µg g -1 dw and 1,034.3 µg g -1 OC). The Santo Antônio Lagoon samples (SA1-4) showed the highest values for both AH and NA.…”
Section: Aliphatic Hydrocarbons and N-alkanesmentioning
confidence: 99%
“…1,40 O índi-ce TAR (terrestrial aquatic ratio) foi proposto originalmente por Bourboniere e Meyers 41 para relacionar a proporção dos n-alcanos de origem terrestre (n-C 29 , n-C 29 e n-C 31 ) e marinha (n-C 15 , n-C 17 e n-C 19 ). Na Baía de Sepetiba, os valores de TAR mais elevados, entre 4 e 9 (Tabela 2), foram encontrados nas mesmas estações nas quais os outros índices de n-alcanos já discutidos (IPC e ACL) também indicam presença de matéria orgânica terrestre.…”
Section: Figura 4 Percentual De 24-etilcolest-5-en-3β-ol (Sitosterolunclassified
“…18,19 Da mesma forma, as informações sobre as fontes de matéria orgânica de origem natural são relativamente restritas. 20 No presente trabalho foi feita a determinação de hidrocarbonetos alifáticos e esterois em sedimentos superficiais com o objetivo de identificar as fontes naturais (autóctonas e alóctonas) e antropogê-nicas (hidrocarbonetos e esgotos domésticos) de matéria orgânica para a Baía de Sepetiba.…”
Section: Introductionunclassified
See 1 more Smart Citation